STUDI EKSPLORATIF HASIL GAMBAR ANAK USIA 4 DAN 6 TAHUN - Hartosujono, Hartosujono (HUMANITAS (Jurnal Psikologi Indonesia), 2012)
This research aimed to compare the picture drawn by children aged 4and 6 year old. 68 students of kindergarten school and in grade one (firstyear) of elementary school involved as participants were asked to draw aperson then assessed based on Florence Goodenough list which revisedby Harrish (1963). To avoid bias, the result of the drawing scored bydrawing teacher and psychology lecturer. Score will be given if there areany similarity score filled in both form in the same child. The result indicatedthat there are differences and similarities between the picture drawn bychildren aged 4 and 6 years old.